Herbicidas para exterminar árboles invasivos en la jardinería doméstica - Kenneth A. Langeland (EDIS, 2006)
SS-AGR-127-S, a 6-page illustrated fact sheet by K.A. Langeland, is the Spanish language version of "Herbicides to Kill Invasive Trees in the Home Landscape." This article discusses methods and herbicides that can be readily used by homeowners for removal of invasive plants and is intended for general information. Includes a table of herbicides used for control of invasive plant species. Published July 2006.